The Missing Middle - Anne O. Krueger (Indian Council for Research on International Economic Relations (ICRIER), 2009)
Though recent economic growth in India has increased productivity and living standards significantly, the need for more growth and more reform remains. Rapid growth of unskilled labor-intensive manufacturing combined with growth of productivity in agriculture is necessary to enable a more inclusive growth that raises living standards in rural areas and in non-agricultural employment of relatively unskilled labor. India's comparative advantage in services does not preclude the need for a rapid-manufacturing growth phase of development due to the service sector's low contribution to output and its demand for educated and skilled, as opposed to unskilled, workers. The failure of manufacturing output and employment to grow more rapidly can be attributed to (1) regulations governing enterprises in the private sector and (2) regulations covering conditions of employment of labor. Reducing the barriers to entry of unskilled labor into manufacturing and relaxing some of the most restrictive labor laws would increase prospects for even faster growth than current high rates.
Keywords: 330